. Which expression is equivalent to (122)6.

A. 1212
B. 128
C. 246

3 answers

B. 128
work
To convert (122)6 to base 10, we can use the formula:

(122)6 = 1*(6^2) + 2*(6^1) + 2*(6^0)
= 1*(36) + 2*(6) + 2*(1)
= 36 + 12 + 2
= 50

Therefore, the expression (122)6 is equivalent to 50 in base 10.

Now, to convert 50 to base 6:

50 / 6 = 8 remainder 2
8 / 6 = 1 remainder 2
1 / 6 = 0 remainder 1

Reading the remainders from bottom to top, we get 122.

Therefore, (122)6 is equivalent to 122 in base 6.

So, the correct answer is not B. 128. Apologies for any confusion.